Case Report: A Rare Case of Autoinflammatory Phospholipase Cγ2 (PLCγ2)-Associated Antibody Deficiency and Immune Dysregulation Complicated With Gangrenous Pyoderma and Literature Review - Wu, Na; Zhang, Bingqing; Wang, Tao; Shen, Min; Zeng, Xuejun (Frontiers in Immunology, 2021)
Background: Autoinflammatory phospholipase Cγ2 (PLCγ2)-associated antibody deficiency and immune dysregulation (APLAID) is a rare autoinflammatory disease caused by gain-of-function mutations in the PLCG2 gene. Methods: The APLAID patient was diagnosed and treated in our department. His phenotype and genotype were documented. A comprehensive literature review on APLAID was also conducted. Results: A 23-year-old Chinese Han man presented with recurrent fever for 18 years and vesiculopustular rashes for 9 years, along with chronic bronchitis, leukocytosis, increased C-reactive protein, immunodeficiency and high serum IgE. A paternal heterozygous missense variant in exon 6 of the PLCG2 gene p. I169V was identified. His vesiculopustular and IgE level responded to medium dose corticosteroids. However, after withdrawn of steroids, he developed severe arthritis and a large deteriorating ulceration resembling pyoderma gangrenosum on the left knee. Then he received adalimumab with satisfactory response for arthritis and skin lesion. Unfortunately, an immunodeficiency-associated lymphoproliferative disorder appeared two months later. Through literature review, a total of ten APLAID patients were reported by six English-language publications. Vesiculopustular rashes, sinopulmonary infection and immunodeficiency were the most frequent symptoms of APLAID. Glucocorticoids, immunoglobulin and biologics were clinically used for treatment, but none of these patients recovered completely. Conclusions: The rarity and diversity of APLAID make it difficult to be diagnosed. Here we reported the first Chinese case of APLAID with gangrenous pyoderma and concomitant high IgE carrying a novel PLCG2 mutation, which may expand the clinical phenotype and genotype of APLAID.